First-year Indonesian EFL University Students’ Reflections about Peer Feedback and Teacher Feedback in Paragraph Writing Course - Sutrisno, Dwi Budidarma; Martora, Jasmal (JURNAL PASIFIK PENDIDIKAN, 2024)
Peer feedback and teacher feedback have been discussed in many scholarly works among researchers of second and foreign language (L2) writing field. This qualitative study aims to explore first-year students’ reflections toward peer feedback and teacher feedback activity in paragraph writing course in Indonesian university. This current research focusing on answer two research questions; 1) How are the students’ reflections of peer feedback in paragraph writing course (2) How are the students’ reflections towards the implementation of teacher feedback in paragraph writing course. The findings show that students have complex opinion about peer feedback because they see it as opportunity to improve their writing through feedback from peers but also perceive it negatively due to how they receive the feedback. However, when it comes to teacher feedback students tend to share positive attitudes and experience as well as tend to prefer teacher feedback compared to peer feedback to some extent.